Decrease in gynecological cancer diagnoses during the COVID-19 pandemic: an Austrian perspective. Issue 11 (8th October 2020) - Tsibulak, Irina; Reiser, Elisabeth; Bogner, Gerhard; Petru, Edgar; Hell-Teutsch, Johanna; Reinthaller, Alexander; Weirather, Cornelia; Weiss, Tatjana; Bozsa, Szabolcs; Puschacher, Barbara; Hall, Mirijam; Hittler, Doris; et al.
Abstract : Background: On March 16, 2020, the federal government of Austria declared a nationwide lockdown due to the COVID-19 pandemic. Since the lockdown, screening examinations and routine checkups have been restricted to prevent the spread of the virus and to increase the hospitals' bed capacity across the country. This resulted in a severe decline of patient referrals to the hospitals. Objective: To assess the impact of the COVID-19 pandemic on the rate of newly diagnosed gynecological and breast cancers in Austria. Methods: Data of 2077 patients from 18 centers in Austria with newly diagnosed gynecological or breast cancer between January and May 2019 and January and May 2020 were collected. Clinical parameters, including symptoms, performance status, co-morbidities, and referral status, were compared between the time before and after the COVID-19 outbreak. Results: Our results showed a slight increase of newly diagnosed cancers in January and February 2020 as compared with 2019 (+2 and +35%, respectively) and a strong decline in newly diagnosed tumors since the lockdown: −24% in March 2020 versus March 2019, −49% in April 2020 versus April 2019, −49% in May 2020 versus May 2019. Two-thirds of patients diagnosed during the pandemic presented with tumor-specific symptoms compared with less than 50% before the pandemic (p<0.001). Moreover, almost 50% of patients in 2020 had no co-morbidities compared with 35% in 2019 (p<0.001). Patients, who already had a malignant disease, were rarely diagnosed with a new cancer in 2020 as compared with 2019 (11% vs 6%; p<0.001). Conclusions: The lockdown led to a decreased number of newly diagnosed gynecological and breast cancers. The decreased accessibility of the medical services and postponed diagnosis of potentially curable cancers during the COVID-19 pandemic may be a step backwards in our healthcare system and might impair cancer treatment outcomes. Therefore, new strategies to manage early cancer detection are needed to optimize cancer care in a time of pandemic in the future.